2019
DOI: 10.1038/s41598-019-46199-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition of Organic-Inorganic Bismuth-Based Perovskite Films for Solar Cell Application

Abstract: Perovskite solar cells have shown a rapid increase of performance and overcome the threshold of 20% power conversion efficiency (PCE). The main issues hampering commercialization are the lack of deposition methods for large areas, missing long-term device stability and the toxicity of the commonly used Pb-based compounds. In this work, we present a novel chemical vapor deposition (CVD) process for Pb-free air-stable methylammonium bismuth iodide (MBI) layers, which enables large-area production employing close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 34 publications
3
51
0
Order By: Relevance
“…Interestingly, in our study both conditions lead to a compact multicrystalline film, but the grain size is highly dependent on the MAI:BiI 3 ratios, changing from crystallites of around 50 nm for film 3, to a crystallite size over 300 nm for film 4. This dependence is also observed in MBI layers deposited by CVD, which grain crystal size increases twofold by increasing the MAI content in the film 36 . www.nature.com/scientificreports/…”
Section: Resultssupporting
confidence: 52%
“…Interestingly, in our study both conditions lead to a compact multicrystalline film, but the grain size is highly dependent on the MAI:BiI 3 ratios, changing from crystallites of around 50 nm for film 3, to a crystallite size over 300 nm for film 4. This dependence is also observed in MBI layers deposited by CVD, which grain crystal size increases twofold by increasing the MAI content in the film 36 . www.nature.com/scientificreports/…”
Section: Resultssupporting
confidence: 52%
“…The first principle calculations based on DFT have revealed that the Bi-based perovskites could be engineered to better bandgaps and have superior absorption coefficients than its lead counterparts. Separately, Sanders et al, have also reported on a novel chemical vapor deposition method to fabricate Bi-based perovskite solar cells that could potentially pave way for large scale and cost-effective commercial markets [87].…”
Section: Bismuth-based Perovskitesmentioning
confidence: 99%
“…[ 19 ] Some research groups have also synthesized phase‐pure MBI perovskite films by various methods, such as solution processing and vapor evaporation, and investigated the surface morphologies, crystal structures, and optoelectronic properties. [ 20,21 ] Jain et al. have reported an increased PCE to 3.17% in Bi based PSCs (Bi‐PSCs), though the MBI perovskite absorber in the n–i–p device structure was thermally evaporated.…”
Section: Introductionmentioning
confidence: 99%